IMPROVING THE VALUE CHAIN IN AGRICULTURE THROUGH THE USE OF DIGITAL TECHNOLOGIES - Kudratova, Iroda Turdibaevna (Western European Studies, 2024)
The article examines the issues of improving digital economic relations in agriculture based on the concepts of IFarming, Agriculture 4.0, Farming 4.0 va Smart Farming related to the digitalization of the value chain, suggests directions and a model for improving the efficiency of the value chain based on digital transformation and digital technologies
Keywords: digitalization; value chain; Farming; Agriculture